Islamic Religious Cues In Indonesian’s Political Debate - Ansar, Fithrah Auliya (Universitas Islam Negeri Raden Intan Lampung, 2016)
Political debate is always used by politician in order to convince the hearer in winning their election. This research aim is to acknowledge the reader about how politician used his language in Political Debate. Many politicians use religious symbols in in performing themselves. Islam, the most majority religion in Indonesia, is always appeared in political debate through appearance or even untterance. This study can give the clearly explanation about Functional semiotic analysis related to language analysis. The theory of Functional analysis can be used in finding the voices of speaker in using their languages. The analysis focused on various features of Islamic symbols in politicians’ utterances and appearances related to the cultural performance. The additional theory about Bakhtinian dialogism was used in order to find the features which are related and different among the debaters. The result showed the features of islamic performance used by each speakers in political debate. The Islamic cues were not only found in non- verbal signs but also existed in verbal utterances.